Syntactic Emphasis Style on Juz 30 (Al-Asalib al-Taukidiyah al-Nahwiyah fi al-Juz al-Tsalatsin) - Eka Siti Namirah; Ibnu Rawandhy N. Hula; Nurul Aini Pakaya (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2022)
This study aims to determine ushlub-ushlub taukid nahwu in chapter 30 of the Qur'an al-Karim. This research is a qualitative descriptive research with library research. Data collection was carried out with documentation from primary sources, namely al-Qur'an al-Karim, and secondary sources which included discussions related to primary sources. The results showed that ushlub taukid nahwu was divided into two, namely taukid bil adat which amounted to 33, and taukid bighairil adat amounted to 101. Researchers found ushlub taukid nahwu in its use amounted to 134. As for taukid bil adat in the number of ismiyah, amounted to 24, the adat used was , , ا, لام التوكيد. While taukid bil adat in fi'liyah number is 9, the custom used is , النوكيد. As for the traditional bighairil taukid, namely ushlub qasm, mashdar, na'at/nature, and athaf